Safety of Ionizing Radiation in Selected Conventional X-ray Diagnostic Centres in Calabar and Uyo metropolises, Nigeria - Ndubuisi O. Chiaghanam; Emmanuel Esien-umo; Michael P. Ogolodom; Caleb Asuquo; Christian Maurice; Efe Omita; Daniel C. Ugwuanyi; Emeka E. Ezugwu (European Scientific Journal, ESJ, 2022)
Background: Humans are inevitably exposed to background radiation in work and public environments. The aim of this work is to assess the effectiveness of the secondary barriers in conventional x-ray diagnostic centers in Calabar and Uyo metropolises. This is by determining the weekly and annual effective dose in their respective uncontrolled areas and comparing them with the international recommendations. Materials and Methods: This cross-sectional study was conducted in three x-ray diagnostic centers in Calabar, represented as C1, C2, and C3 respectively, and in four xray diagnostic centers in Uyo, represented as U1, U2, U3, and U4 respectively. Background radiation was measured using Radex 1212 A-A battery-powered survey meter, at a distance of 2.5meters away from the xray units. Radiation measurement was taken at three different spots, and the recorded data were analyzed. Results: The mean calculated effective dose per week in mSv/week for each diagnostic center was given as 0.130 ± 0.0068mSv/week. Also, the mean calculated effective dose per year in mSv/year for each center was given as 0.66 ± 0.35mSv/year. These values are below the National Commission on Radiation Protection (NCRP) recommendations of 0.02mSv/week and 1mSv/year respectively. From the results, the mean calculated chance of developing cancer was 2.33 ×10-3% which was lower than the NCRP recommendation for continuous public exposure of 5.5×10-3 %. Conclusion: It could be concluded that the integrity of the shielding designs and their dimensions assessed are safe.